PENILAIAN DAN PENELUSURAN KINERJA TENAGA PENDIDIK DAN KEPENDIDIKAN - Ahmad Badwi (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2020)
This article discusses the problem of Evaluating and Tracking Performance of Educators and Education Personnel with a literature approach. From the results of the assessment obtained that understanding; 1) An Educator and Education must be able to know what has been their responsibility, not to underestimate the rights and obligations agreed upon. 2) To get or produce qualified Educators and Education staff there are several strategies that might be implemented, namely: Self Assessment, Formulation of Vision, Mission, and Objectives, Planning, Implementation, Evaluation, and Reporting. And an educator and educator must be able to maximize their duties and obligations correctly and full of responsibility.